Vitamin D Levels and its Influence on Maternal Blood Glucose, Blood Pressure, and Fetal Weight - Reza, Hanif; Soraya, Yulice; Makarim, Fadhli Rizal; Alfarizi, Rizki (Publikasi Indonesia, 2025)
Vitamin D is essential for various physiological functions. Vitamin D deficiency is a global concern, including vitamin D deficiency during pregnancy. Maternal vitamin D deficiency is associated with an increased risk of adverse gestational outcomes. The objective of this cross-sectional study is to examine the impact of maternal Vitamin D levels on blood sugar, blood weight, and fetal weight. The study used quantitative method. Twenty-six women with gestational age 12-16 weeks as participants of this study were recruited from two Primary health care in Semarang, Indonesia between September - October 2023 were analyzed for serum 25-hydroxy Vit. D (25(OH)D). The samples then were evaluated for blood glucose, blood pressure and fetal weight using ultrasonography. The results of the Pearson's correlation rank test for Vitamin D with estimated fetal weight, blood glucose, systolic blood pressure, and gestational ages as covariate showed P>0.05, It implies that there is no relationship between Vit. D and other variables. Our study showed level of Vitamin D has no influence on of blood glucose level, incidence of hypertension, and low fetal weight.